Astronomical Observations Support Dirac’s Hypothesis of Matter Creation Caused by Quantum Fluctuations - Eriksson, Jarl-Thure (European Journal of Applied Sciences, 2025)
Recent astronomical observations have questioned the validity of the Big Bang theory. Well-known physicists Arthur Eddington, Fred Hoyle and Paul Dirac strongly opposed the paradigm. Black holes are described as objects that prevent light from escaping due to gravitational force. Little attention has been paid to the possible extraordinary properties of such objects. Here, the universe is considered as a black hole. The Schwarzschild radius stands for the outer event horizon, whereas the real radius is half thereof. The negative potential energy of any object on the interface equals the mass energy of said object. We postulate that inside a black hole, positron-electron pairs evolve as a certain fraction of the Planck energy. On the outside of a black hole in the galaxy center, proton-antiproton pairs are ejected, creating baryonic matter. The creation of matter increases the space. Outside the universe there is no space, instead of space, time is created. The current CBU-model (Continuously Breeding Universe) explains dark energy and dark matter. Moreover, it changes the relationship between the redshift and the scale factor, bringing light sources closer to the present. As a result, the Hubble tension and the age of early galaxies are explained. The CBU model predicts that time and photons are quantized.